Specific contents of one side, pedagogical contents of another: a dilemma that has not been overcome in the training courses for the geography teacher - Silva, Alcinéia de Souza; Cunha, Leonardo Ferreira Farias da (Geosaberes; Vol 9 No 18 (2018): May - Aug.DO - 10.26895/geosaberes.v9i18.632, 2018)
This paper aims to analyze and discuss the curricular organization of the degree course in Geography of a Teaching Institution in the city of Formosa-GO. The text discusses issues that involve the role of the curriculum in the project of initial teacher training, the dilemmas still not overcome by the training courses and the necessary knowledge for this professional to develop their pedagogical practice. Through documentary analysis (Pedagogical Project of the Course - PPC), it was observed the fragmentation and disarticulation between the specific contents and the pedagogical contents in the pedagogical proposal of that Institution. Faced with such a reality, there is an urgent need for bachelor´s degrees, in general, to rethink and reorganize their curricula in order to achieve a solid, meaningful academic education connected to teaching work in schools.